Effect of Biodiesel Candlenut Seed (Aleurites Moluccana) to NOx Emission and Combustion Process on Single Cylinder Diesel Engine - Cahyono, Beny; Fathallah, Aguk Zuhdi Muhammad; Pujinaufal, Vianto Ilham (International Journal of Marine Engineering Innovation and Research, 2025)
Fossil fuels are non-renewable fuels but are still the main fuel choice however, it is now becoming increasingly recognized that the availability of fossil fuels are dwindling which further encourages research on renewable fuels. One of the renewable fuels under development and research is biodiesel. The use of vegetable and animal oil is one of the primary choices to decrease the use of non-renewable fuels. Candlenut oil is one of the alternatives under research and development to produce biodiesel as a replacement for non-renewable fuels. In this research is expected to know the NOx emission level and combustion process of single cylinder diesel engine using candlenut oil biodiesel and compared with diesel fuel High-Speed Diesel (HSD). The results of NOx emission comparison between biodiesel candlenut and HSD showed an increase of 0.76 gr / kWh for biodiesel candlenut and 0.51 gr / kWh for HSD fuel. In the burning process test results showed the knocking value of better candlenut biodiesel than HSD which is 5.69 bar for biodiesel candlenut and 6.19 bar for HSD fuel.